2000
DOI: 10.1523/jneurosci.20-08-02988.2000
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Separation of Two Behavioral Phenotypes by a Mutation Affecting the Promoters of a Ca-Activated K Channel

Abstract: The Drosophila slowpoke gene encodes a BK-type calcium-activated potassium channel. Null mutations in slowpoke perturb the signaling properties of neurons and muscles and cause behavioral defects. The animals fly very poorly compared with wild-type strains and, after exposure to a bright but cool light or a heat pulse, exhibit a "sticky-feet" phenotype. Expression of slowpoke arises from five transcriptional promoters that express the gene in neural, muscle, and epithelial tissues. A chromosomal deletion (ash2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 31 publications
1
57
0
Order By: Relevance
“…This observation is further supported by the analysis of ash2 18 /ϩ flies carrying a lethal inversion that exclusively removes the neural promoters away from the slo locus, leaving the remaining intact (33). This inversion has been shown to complement only the muscle-associated defects of slo 4 (28). Fig.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…This observation is further supported by the analysis of ash2 18 /ϩ flies carrying a lethal inversion that exclusively removes the neural promoters away from the slo locus, leaving the remaining intact (33). This inversion has been shown to complement only the muscle-associated defects of slo 4 (28). Fig.…”
Section: Resultsmentioning
confidence: 69%
“…A null mutation in the slo locus strikingly alters the electrical properties of both neurons and muscles (22)(23)(24), affecting neurotransmitter release (25) and thereby causing a variety of behavioral defects among those in courtship behavior (26)(27)(28). We have previously demonstrated that a slo null mutant is behaviorally arrhythmic under free-running [constant darkness (DD)] conditions (13).…”
mentioning
confidence: 99%
“…In particular, differential expression of alternatively spliced BK type Ca 2+ -activated K + channels are known to be of physiological importance (i.e. Atkinson et al, 2000;Rosenblatt et al, 1997), and an interesting hypothesis is that differential expression of a specific SLO-1 isoform in M4, in the Rhabditidae family, is critical for inactivating M4-TB synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct transcripts can shape the channel properties to the requirements of the cells, tissue, developmental stage or physiological state. In Drosophila, tissue-specific transcriptional promoters (Atkinson et al, 2000;Brenner et al, 1996) and alternative splicing (Adelman et al, 1992;Derst et al, 2003;Lagrutta et al, 1994) generate a large number of transcripts that could modify channel properties such as singlechannel conductance, calcium sensitivity and mean open time (Adelman et al, 1992;Lagrutta et al, 1994). In vertebrates, alternatively spliced BK transcripts are expressed in distinct patterns in the brain (Tseng-Crank et al, 1994), cochlea (Jiang et al, 1997;Langer et al, 2003), kidney (Bravo-Zehnder et al, 2000) and smooth muscle of arteries, esophagus and uterus (Knaus et al, 1994;Salapatek et al, 2002;Zhou et al, 2000), suggesting isoform-specific functions.…”
mentioning
confidence: 99%